Pengaruh Penerapan Green Accounting, Profitabilitas, Leverage, Ukuran Dewan Komisaris, dan Pengungkapan Media Pada Pengungkapan CSR - Kondo, Agnes Monika Febrianti; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi; Vol 34 No 8 (2024)DO - 10.24843/EJA.2024.v34.i08.p06, 2024)
Corporate Social Responsibility (CSR) is a form of corporate responsibility to stakeholders and the community because of the damage caused by the company's operations. The purpose of this study is to empirically prove the effect of the application of green accounting, profitability, leverage, size of the board of commissioners, and media disclosure on CSR disclosures in mining companies which successively during the 2016-2020 period received PROPER awards from the Ministry of Environment and Forestry with  40 samples. Data collection is done by literature study. The data collected were analyzed using multiple linear regression analysis. The results show that green accounting and media disclosure have a significant positive effect on CSR disclosure, profitability and leverage have a negative effect on CSR disclosure, the size of the board of commissioners has no significant effect on CSR disclosure. Keywords : Green Accounting, Size of the Board of Commissioners, Media Disclosure, Corporate Social Responsibility